A Rare Case of Bronchopulmonary Infection by Lophomonas Blattarum : A Case Report - Arun Kumar Mahato; Sonu Shah; Rupak K C; Sudarshan Kandel; Neetika Paudel; Saharoj Siddiqui; Niranjan K C (Journal of Nepal Medical Association)
Lophomonas blattarum is a flagellated protozoan parasite found in cockroaches' and termites' hindgut. It can rarely cause bronchopulmonary infection in humans, especially in people with other comorbidities or immunocompromised, but the prevalence and characterization of the disease remains poorly understood. In this case report, we present a case of a 51-year-old male patient with underlying Hepatitis B presenting with a persistent cough for more than two weeks. During evaluation, microscopic examination of the wet mount of Bronchoalveolar lavage revealed actively motile trophozoite of Lophomonas blattarum. The patient was treated with metronidazole with significant improvement in two weeks.